“They sing, study together and treat the disabled person as just another member of the group” (Journal of Parents and Teachers, 2026)
Cristo Rey School runs a programme for pupils with special educational needs, Down’s syndrome or autistic traits. This pioneering initiative combines individualised support with participation in mainstream classes. Furthermore, it prioritises inclusion over academic achievement.
Keywords: Special needs; School, Inclusion; Individualised support